An alternative treatment for Candida infections with Nigella sativa extracts. Issue 2 (12th March 2012) - Bita, A.; Rosu, A.F.; Calina, D.; Rosu, L.; Zlatian, O.; Dindere, C.; Simionescu, A.
Abstract : Background: Nigella sativa is a herb from the Mediterranean region with antidiabetic, bronchodilator, antioxidant, hepatoprotective, lipid lowering, anti-inflammatory and analgesic properties. Purpose: This study aimed to reveal the antifungal activity of aqueous, methanolic and chloroform extracts obtained from the plant seeds, compared with the effect of traditional antifungals. Materials and methods: Using standard mycological diagnostic methodology The authors isolated and identified 20 strains of Candida albicans from pathological products collected from patients hospitalised in different departments of the Craiova Emergency Hospital. Aqueous, methanolic and chloroform extracts were made from the seeds of Nigella sativa, in decreasing dilutions, in which Wattman filter paper discs were soaked and dried and then used to achieve the antifungal graph by using the Kirby-Bauer diffusion technique. Simultaneously, the testing was repeated using standard antifungal disks (Becton Dickinson) and the two sets of results compared. The antifungal effect was assessed by measuring the diameter of the inhibition zone, noting the concentration per disk. Results: The results show that methanolic extracts of Nigella sativa have the strongest antifungal effect followed by the chloroform extracts. Aqueous extracts showed no antifungal activity. Conclusions: The research shows treatment with natural products in a good light as an alternative for treating fungal infections. The authors envisage Nigella sativa extract enhancing the effect of conventional therapy.